2019
DOI: 10.3389/fphys.2019.00074
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Lead Placement in the Right Ventricle During Cardiac Resynchronization Therapy. A Simulation Study

Abstract: Patients suffering from heart failure and left bundle branch block show electrical ventricular dyssynchrony causing an abnormal blood pumping. Cardiac resynchronization therapy (CRT) is recommended for these patients. Patients with positive therapy response normally present QRS shortening and an increased left ventricle (LV) ejection fraction. However, around one third do not respond favorably. Therefore, optimal location of pacing leads, timing delays between leads and/or choosing related biomarkers is crucia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 105 publications
1
21
0
Order By: Relevance
“…The geometry of the ischemic central zone (ICZ) and border zone (BZ) was obtained based on the gray intensity of each pixel [4] ( Figure 1). The His-Purkinje system (HPS) network used in this work was the same network developed in our previous study [5]. It comprises two and three main branches in its right and left section, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The geometry of the ischemic central zone (ICZ) and border zone (BZ) was obtained based on the gray intensity of each pixel [4] ( Figure 1). The His-Purkinje system (HPS) network used in this work was the same network developed in our previous study [5]. It comprises two and three main branches in its right and left section, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Our simulations were performed using a modified version of the O'Hara ventricular action potential model [6], that includes the changes described in our previous work [5]. Alteration caused by acute ischemia was introduced in the model by modifying and incorporating several currents.…”
Section: Methodsmentioning
confidence: 99%
“…However, post hoc analysis in large studies demonstrated no differences in cardiac remodeling and clinical endpoints in patients who underwent CRT irrespective of placement of the right ventricular electrode at the apex or septum [18]. A computer simulation of Biventricular pacing found that the right ventricular upper septum near the outflow tract was an alternative location for the right ventricular apex leads [19]. More clinical trials are needed to accumulate strong evidence regarding the positioning of the right ventricular electrode.…”
Section: Implantation Of Right Ventricular Electrodementioning
confidence: 99%
“…Although CRT has been very extensively studied little attention has been made of the right ventricular lead position. A theoretical mathematical model suggested the optimal LV lead position was dependent upon the position of the RV lead . For example, a RV high septal/outflow tract lead position worked best with the LV lead in the lateral wall whereas with the lead at RVA the optimal LV lead location was at the epicardial LV antero‐basal wall.…”
Section: Cardiac Resynchronization Therapy (Crt)/biventricular Pacingmentioning
confidence: 99%